HUBUNGAN ANTARA STATUS GIZI DENGAN KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT (ISPA) PADA BALITA BULAN JANUARI-DESEMBER 2023 DI RUMAH SAKIT UMUM DAERAH TONGAS PROBOLINGGO - Devandra Vijaya Putra, Ida bagus; Retno Arimbi, Muzaijadah; Haryanti, Elizabeth; Kuntaman (Calvaria Medical Journal, 2026)
Background: Child development problems in Indonesia and other developing countries are generally caused by two things: malnutrition and infectious diseases. An infectious cause that continues to be a problem in children is respiratory infections. Respiratory tract infections attack the upper and lower respiratory tract. In infants, the immune system is not yet optimal and is easily infected with various diseases including ARI. Objective: This study aims to determine the relationship between nutritional status and the incidence of acute respiratory infections (ARI) in toddlers. Method: This study was conducted with observational analytic method with cross sectional approach. Results: The results of this study showed that toddler patients with ARI in Tongas Probolinggo Hospital were dominated by female patients (51.7%), male patients (48.3%). The age of patients who dominated is age 1-2 years (60.0%) and 3-4 years (40.0%). The types of patients based on nutritional status were well-nourished patients (53.3%) undernourished (26.7%) and malnourished 12 people (20.0%). Diagnosis of the disease Non-ARI (33.3%) and ARI (66.7%). The data results using the chi square method showed a p value of 0.001 < α = 0.05, so it can be concluded that H0 is rejected, H1 is accepted. Conclusion: There is a significant relationship between nutritional status and the incidence of acute respiratory infections (ARI) in toddlers in January - December 2023 at Tongas Regional General Hospital, Probolinggo.